1991
DOI: 10.3109/09553009109169316
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of repair of DNA double-strand breaks caused by neutron or gamma radiation in cultured human cells

Abstract: The dose-response for the induction of initial double-strand breaks (dsb) in DNA of human epithelioid cells by JANUS 0.85 MeV fission-spectrum neutrons was parabolic as assayed by a calibrated neutral filter elution technique. The relative biological effectiveness (RBE) of these neutrons relative to 60Co gamma-rays was unity. The kinetics of repair after a 60 Gy gamma-ray exposure were biphasic. About 65% of these dsb were rapidly repaired (T 1/2 of approximately 2 min), and the remainder were almost completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The rejoining of double-strand breaks as a function of time shows a slow and fast component [112]. A higher proportion of double-strand breaks remain unrejoined after exposure to high-as opposed to low-LET radiation [46,61], and the lethality of double-strand breaks increases profoundly with the LET up to a maximum and then decreases [113].…”
Section: Dna Base Damage Repairmentioning
confidence: 99%
“…The rejoining of double-strand breaks as a function of time shows a slow and fast component [112]. A higher proportion of double-strand breaks remain unrejoined after exposure to high-as opposed to low-LET radiation [46,61], and the lethality of double-strand breaks increases profoundly with the LET up to a maximum and then decreases [113].…”
Section: Dna Base Damage Repairmentioning
confidence: 99%
“…As the search for more sensitive and reliable predictive assays continues in the clinic and for radiation protection, an important determinant of cellular radiosensitivity is DNA repair proficiency (Weichselbaum 1986, Fox and McNally 1988, Peak et al 1991, Hu and Hill 1996, Britten and Murray 1997, Dolling et al 1998. As in the case of MN and apoptosis data, the conclusions of numerous DNA damage induction and repair studies are diverse and appear to be cell type dependent (Whitaker et al 1991, Smeets et al 1993, Olive et al 1994, Ruiz de Almodovar et al 1994, Dikomey et al 1998, Roos et al 2000, Theron et al 2000, Serafin et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Repair of DSBs in mammalian cells seems to occur with a fast and a slow component (25)(26)(27). It has generally been found that DSBs induced by higher-LET radiation are repaired more slowly, with a larger fraction of nonrejoined breaks remaining several hours after irradiation (11,13,26,(28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…It has generally been found that DSBs induced by higher-LET radiation are repaired more slowly, with a larger fraction of nonrejoined breaks remaining several hours after irradiation (11,13,26,(28)(29)(30)(31)(32). This has been interpreted to mean that DSBs induced by high-LET radiation are more complex and difficult to repair.…”
Section: Introductionmentioning
confidence: 99%